Discovery and Verification of Gelsolin as a Potential Biomarker of Colorectal Adenocarcinoma in a Chinese Population: Examining Differential Protein Expression using an Itraq Labelling-Based Proteomics Approach - Nai-Jun Fan; Chun-Fang Gao; Chang-Song Wang; Jing-Jing Lv; Guang Zhao; Xin-Hua Sheng; Xiu-Li Wang; Dong-Hui Li; Qing-Yin Liu; Jian Yin (Canadian Journal of Gastroenterology)
Despite the wide range of available colorectal cancer (CRC) screening tests, less than 50% of cases are detected at early stages. However, the identification of differentially expressed proteins or novel protein biomarkers in CRC may have some utility and, ultimately, improve patient care and survival. Proteomics combined with mass spectroscopy and liquid chromatography are emerging as powerful tools that have led to the discovery of potential markers in cancer biomarker discovery in several types of cancers. This article describes a novel technology that uses isotopic reagents to tag selected proteins that show a consistent pattern of differential expression in CRC.